Enterprise Resource Planning (ERP) System and Company Performance - Wong, Zheng Hua (2011)
Enterprise resources planning (ERP) system, from business perspective, is following the need for integration of company's information in the real time environment as one of key success factors in strategic and operational decision making process. This research paper was conducted to identify and evaluate for the ERP system implementation in Jabil Green Point in term of the performance's improvement. Operations performance was treated as the dependent variables while Control, Integration and Contagion were the independent variables respectively. The Control variable was measured with respect to the ERP ability in control for the cost and inventory. Integration variable was measured in term for the system to integrate various functions in Jabil Green Point. Contagion variable was measured the connection between the organization's cultural and the ERP system implementation. A total of 50 respondents from the population of 65 staff in Jabil Green Point participated in this research paper. The data collection was conducted through the distribution of questionnaires, which was designed to measure the operations performance with a statement on a five likert scale point, ranging from one (strongly disagree) to five (strongly agree). Three hypotheses were tested for this research paper. Data was analyzed using the SPSS software to obtain the frequencies, means, median, standard deviation and correlations between variables. Descriptive analysis, Reliability analysis and Correlation & Relationship analysis were conducted to test the data collected. The results show that the Control and Integration variables have the positive relationship with operations performance while Contagion variable stated for the negative relationship with operations performance. In conclusion, this research paper shows that successfully for the ERP implementation were resulted in the improvement of the organization's performance. The suggestion for the future research was the research study have to involved for more companies especially for the multinational companies, thus the statistical generalization can be made.